(untitled) (Research, Society and Development, 2025)
Introduction: Pancreatectomy is the surgical procedure considered the first line of choice for refractory chronic pancreatitis, locoregional metastases and benign and malignant neoplasms, and may vary anatomically in its proposal, between central, distal or total pancreatectomy. Methodology: The current study is a narrative review, with a time limitation for the last 5 years (2019-2024) which resulted in 780 articles, of which 59 were used as a source of information. Discussion: Laparoscopic distal pancreatectomy is a surgical procedure indicated to treat, mainly, pancreatic endocrine neoplasms, especially NEM1, intraductal papillary mucinous neoplasms, insulinomas and mucinous cystic neoplasms. The indication for the procedure is prior to preoperative classifications, for example, the tumor and splenic vein relationship that assesses the extent of the relationship between scale I to IV variables. In addition, the possibility of the approach being total, distal or central, being previously known in 6 stages among the different techniques. The main complications are pancreatic fistula, hemorrhage, endocrine insufficiency, site infection, sepsis and deep vein thrombosis, which may be in increased prevalence due to the risk factors of advanced age, fatty infiltration of the pancreas, pre-existing diabetes mellitus and use of previous anticoagulants. Conclusion: Laparoscopic pancreatectomy is a minimally invasive surgical technique with extensive advances in reducing complication events, in addition to successive improvements in the assessment of benefits due to reduced risks.